Weight-bearing cone-beam computed tomography in the foot and ankle specialty: where we are and where we are going - an update - Godoy-Santos,Alexandre Leme (2021)
Abstract Cone-beam computed tomography (CBCT) has been applied in dentistry and medicine for nearly two decades. Its application in the foot and ankle specialty has grown exponentially in recent years. Weight-bearing CBCT allows clinicians to obtain weight-bearing images that can be viewed in all three planes and to construct three-dimensional models, similar to those constructed from traditional CT scans, as well as exposing patients to less radiation than do traditional CT scans. This technology has revolutionized diagnoses, improving the understanding of various lesions and surgical planning in the foot and ankle specialty. Ongoing studies of the use of weight-bearing CBCT in foot and ankle surgery are focused on fully automated and semi-automated three-dimensional measurements, as well as bone segmentation, mapping of the distances/orientation of the joints, and the production of customized implants. The aims of this review article are to show the evolution of this emerging tool in the foot and ankle specialty, to update those in related specialties on its use in current clinical practice, and to indicate where the research community is heading.